DIGITAL TOOLS TO MAKE ASIAN CENTURY A REALITY - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 11 May 2016 – A digital economy can be an important tool to tackle the harmful challenges that would affect the rise of the world economy, particular in Asia, as highlighted by Dr. Keiichiro Oizumi, a Senior Economist from the Japan Research Institute during his public lecture, entitled "Mega Trends in East Asia What is Happening? What’ll Happen?" here recently.